Faculty members/course instructors' incorporation of service-learning within their teaching: understanding motivating factors and perceptions of institutional support - Balgopal, Anita, author; Kuk, Linda, advisor; Anderson, Sharon, committee member; Banman, Nancy, committee member; Miller, Lisa, committee member (Colorado State University. Libraries, 2014)
This study sought to understand why a select group of faculty members and course instructors are motivated to incorporate a service-learning component within their teachings. It explored how they incorporated this teaching approach within their course curriculum and research agenda. The study also examined the participants' perception as it pertained to institutional support and resources availability when creating and maintaining service-learning courses. All participants worked at a large, Midwestern, research extensive, Land Grant institution. As an eligibility criterion, the group of faculty members and instructors were all recognized for their achievements in incorporating a service-learning component within their course curriculum by the public engagement unit on their campus. The study employed collective case study methodology and seven faculty members/instructors participated in in-depth interviews. All seven participants identified that service-learning courses encompass three elements: (i) gaining knowledge; (ii) applying knowledge; and, (iii) reflecting on the experience. Participants were intrinsically motivated by four factors to incorporate service-learning within their curriculum: (1) student success; (2) school mission and values; (3) meeting societal needs; and, (4) self values pertaining to community engagement. And although participants recognized support by the institution, unit support for incorporating service-learning within their curriculum was lacking. Study implications identified that service-leaning instructors need to be recognized and rewarded and appropriate university resources should be allocated to support these endeavors.
Keywords: service learning; perceptions; support; faculty members; motivation